Chronic intestinal pseudoobstruction and ophthalmoplegia in a patient with mitochondrial myopathy. Issue 4 (April 1988) - Cervera, R; Bruix, J; Bayes, A; Blesa, R; Illa, I; Coll, J; Garcia-Puges, A M
Abstract : A 38 year old woman having chronic intestinal pseudoobstruction associated with mitochondrial myopathy is reported. The clinical and radiographic features suggested the diagnosis of chronic intestinal pseudoobstruction. Muscular atrophy and ophthalmoplegia led to muscle biopsy, which disclosed accumulation of normal and abnormal mitochondria ('ragged red fibres'), characteristic of mitochondrial myopathy.